LONG-TERM RESULTS OF PATIENTS WITH DEFORMATION OF THE ANTERIOR ABDOMINAL WALL AFTER ABDOMINOPLASTY - Khudaiberganova , N.Sh. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Abdominoplasty remains one of the urgent problems in modern abdominosurgery. The relevance is associated with an increase in the number of patients with obesity, ptosis in women after childbirth and in patients with recurrent ventral hernias. We have studied 413 patients, of which 204 are control, 209 are the main group. The developed method of abdominoplasty provides less trauma, preservation of anatomical structures, and short rehabilitation periods. The development and application of a therapeutic and diagnostic algorithm for surgical correction of various types of deformity made it possible to avoid cases of recurrence of deformity, to increase the level of lung capacity elimination of complications in the immediate postoperative period with a decrease in the frequency of their development by 2.4% and increase the number of good results with the achievement of an aesthetic and functional effect by 21.7%.